2006
DOI: 10.1002/pon.1062
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of the impact of genetic susceptibility testing for BRCA1/2 or HNPCC on family relationships

Abstract: This study assessed the impact of genetic testing for cancer susceptibility on family relationships and determinants of adverse consequences for family relationships. Applicants for genetic testing of a known familial pathogenic mutation in BRCA1/2 or a HNPCC related gene (N=271) rated the prevalence and nature of changes in family relationships, familial difficulties and conflicts due to genetic testing 6 months after receiving the test result. The level of family functioning, differentiation from parents, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 26 publications
3
56
0
1
Order By: Relevance
“…[20][21][22][23][24][25]27 These studies have also reported, similar to this study, more positive than negative family relationship effects. [20][21][22]24,27 Taken together, these results offer reassurance about potential family effects to individuals considering BRCA1/2 testing. The association between psychological adjustment difficulties, such as cancer distress and intolerance for uncertainty, and the more frequent reporting of positive effects of genetic testing is intriguing.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…[20][21][22][23][24][25]27 These studies have also reported, similar to this study, more positive than negative family relationship effects. [20][21][22]24,27 Taken together, these results offer reassurance about potential family effects to individuals considering BRCA1/2 testing. The association between psychological adjustment difficulties, such as cancer distress and intolerance for uncertainty, and the more frequent reporting of positive effects of genetic testing is intriguing.…”
Section: Discussionsupporting
confidence: 89%
“…25,27 In the months following the test result disclosure, a decrease in the level of family cohesion and expressiveness have also been reported. 26,28 To the best of our knowledge, no study has yet evaluated how other sociodemographic, medical, and psychosocial characteristics are associated with the incidence of long-term effects on family relationships in the context of BRCA1/2 genetic testing.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Disclosing the genetic test results to at-risk family members can be a time consuming and emotionally laden process for the patient, and patients can experience feelings of guilt regarding the possibility of passing on to their children a hereditary predisposition to breast and ovarian cancer. 23 Patients faced with both of these sets of challenges simultaneously could become overwhelmed. Genetic testing could get lost in the shuffle of complicated medical care and other immediate decisions that need to be made.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence strongly suggests that reciprocal social support, compared to one-way provision or receipt of support, are especially important on the well-being of older adults (Heaney and Israel 2008;House et al 1988). Previous studies showed that social support exchanges among family members were associated with communication of disease risks within the family (Hughes et al 2002;Koehly et al 2009;van Oostrom et al 2007a). Thus, it is possible that the extent to which reciprocal social support exchange occurs within family systems determines older adults' desire and ability to share FHH information with family members.…”
Section: Sharing Family Health History (Fhh) Informationmentioning
confidence: 99%